Simultaneous Whole-Chamber Non-contact Mapping of Highest Dominant Frequency Sites During Persistent Atrial Fibrillation: A Prospective Ablation Study - Chu, Gavin S.; Li, Xin; Stafford, Peter J.; Vanheusden, Frederique J.; Salinet, João L.; Almeida, Tiago P.; Dastagir, Nawshin; Sandilands, Alastair J.; Kirchhof, Paulus; Schlindwein, Fernando S.; Ng, G. André (Frontiers in Physiology, 2022)
Purpose: Sites of highest dominant frequency (HDF) are implicated by many proposed mechanisms underlying persistent atrial fibrillation (persAF). We hypothesised that prospectively identifying and ablating dynamic left atrial HDF sites would favourably impact the electrophysiological substrate of persAF. We aim to assess the feasibility of prospectively identifying HDF sites by global simultaneous left atrial mapping. Methods: PersAF patients with no prior ablation history underwent global simultaneous left atrial non-contact mapping. 30 s of electrograms recorded during AF were exported into a bespoke MATLAB interface to identify HDF regions, which were then targeted for ablation, prior to pulmonary vein isolation. Following ablation of each region, change in AF cycle length (AFCL) was documented (≥10 ms considered significant). Baseline isopotential maps of ablated regions were retrospectively analysed looking for rotors and focal activation or extinction events. Results: 51 HDF regions were identified and ablated in 10 patients (median DF 5.8Hz, range 4.4-7.1Hz). An increase in AFCL of was seen in 20 of the 51 regions (39%), including AF termination in 4 patients. 5 out of 10 patients (including the 4 patients where AF termination occurred with HDF-guided ablation) were free from AF recurrence at 1 year. The proportion of HDF occurrences in an ablated region was not associated with change in AFCL (τ=0.11, p=0.24). Regions where AFCL decreased by 10 ms or more (i.e. AF disorganization) after ablation also showed lowest baseline spectral organization (p<0.033 for any comparison). Considering all ablated regions, the average proportion of HDF events which were also HRI events was 8.0±13%. Focal activations predominated (537/1253 events) in the ablated regions on isopotential maps, were modestly associated with the proportion of HDF occurrences represented by the ablated region (Kendall’s τ=0.40, p<0.0001), and very strongly associated with focal extinction events (τ=0.79, p<0.0001). Rotors were rare (4/1253 events). Conclusion: Targeting dynamic HDF sites is feasible and can be efficacious, but lacks specificity in identifying relevant human persAF substrate. Spectral organization may have an adjunctive role in preventing unnecessary substrate ablation. Dynamic HDF sites are not associated with observable rotational activity on isopotential mapping, but epi-endocardial breakthroughs could be contributory.